The Impact of Management Information Systems on Construction Project Management: An Applied Study on the Qiddiya Project (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aimed to explore the reality of management information systems (data collection and processing, information storage and retrieval, material and human requirements) and their impact on the management of construction projects in the Qiddiya project in the Kingdom of Saudi Arabia. The study included a community of 230 managers, and a random sample of 140 managers was selected. Questionnaires were distributed to the sample, and 105 questionnaires were retrieved with a response rate of 75.3%. The results of the study showed a statistically significant impact at the significance level of management information systems (human and material requirements) on the management of construction projects in the Qiddiya project. The results also showed that the sub-variables (human and material requirements) have a significant impact on directing and managing projects and ensuring the quality of performance. While there was no statistically significant impact of the sub-variables related to data collection, processing, storage and retrieval on the management of construction projects as a dependent variable. The study recommended the need to enhance the activation of management information systems by organizing training courses and awareness workshops that highlight their importance and role in improving the efficiency of implementing construction projects.
Keywords: Management Information Systems; Construction Project Management; Qiddiya Project; Kingdom of Saudi Arabia